Effect of thiourea on physiological performance of two salt affected rice (Oryza sativa L.) cultivars - Zahra, Syeda Maasooma; Wahid, Abdul; Maqbool, Nazimah; Ibrahim, Mohd Hafiz (Sciencedomain International, 2018)
Aims: The aim of the experiment was to investigate the effect of thiourea on physiological characteristics of two rice (Oryza sativa L.) varieties under impact of salinity. Study Design: Experiment includes two rice varieties named as B-515 and KS-282, salinity level of 150 mM, thiourea of 0.25 mM alone and in combination were arranged in a completely randomized design (CRD). Place and Duration of Study: Old Botanical Garden, University of Agriculture Faisalabad, Pakistan, between 4th July and 21st August 2015. Methodology: Transplants of two rice varieties, Basmati-515 and KS-282 were exposed to salinity (150 mM) and thiourea (0.25 mM) after one month of transplanting in a Completely Randomized Design with three replications. Harvesting data was taken that include fresh and dry weights, leaf area, number of tillers, photosynthetic pigments, photosynthetic rate, transpiration rate, stomatal and substomatal conductance, water use efficiency and intrinsic CO2 concentration as well as chlorophyll contents in two rice varieties. Results: Thiourea treatment enhanced photosynthetic efficiency of Basmati-515 more than KS-282 by improving the chlorophyll and carotenoid contents and gas exchange attributes more than control. Conclusion: Salinity profoundly affect the physiological performance of two rice varieties especially that of KS-282, while 0.25 mM thiourea application unable to mitigate the effect of salinity but thiourea alone proved to be beneficial for both the rice varieties.